Literatura chorwacka w neokapitalysticzney artykulacji - Duda, Dean (Array, 2005)
Starting from a critique of Croatian literary scholarship, which due to its lack of interest in the media culture of post-industrial capitalism cannot describe the structural changes that have occurred in the public life of Croatian literature, this paper uses certain insights of cultural studies and the critical political economy of culture in an attempt to define the reasons that caused literature in the situation of transition to change the nature of its public presence, gaining a high media profile in the process. The analysis begins with the Festival of Alternative Literature (FAK), which, being a phenomenon that belongs to both literary and popular club culture, opened up the process of media reproduction of literature. The media corporations have meanwhile seized the opportunity offered by the initial stages of cultural industry and a newfound social interest in literature by launching a series of projects of selling ? ; books with newspapers? ; . The initial dynamics of Croatian literature and publishing were thus brought into a number of new and contradictory relations. The aim of this paper is to point out the complex problems that the context of transition creates for the study of literature, arguing that the change in the position of literature within the framework of new social relations should of necessity affect the discursive practices used to analyze it.